2015
DOI: 10.1080/11250003.2015.1080312
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes and rotifers on two Alpine debris-covered glaciers

Abstract: Debris-covered glaciers (DCGs) are glaciers whose ablation area is mostly covered by a continuous layer of debris, and are considered to be among the continental glacierized environments richest in life. DCG colonization by microorganisms, plants and animals, has been investigated in a few studies, while the meiofauna (metazoans smaller than 2 mm) of these environments has been neglected so far. In this study, we analyzed nematode and rotifer fauna on the two largest debriscovered glaciers of the Italian Alps:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…For instance, nematodes survive freezing and desiccation in Antarctic soils through dormancy but reproduce when water and temperature conditions are favourable (Wharton, 2003). The presence of nematodes overlying glaciers in supraglacial debris (Azzoni et al ., 2015) and in glacier mice (Coulson & Midgley, 2012) indicates the presence of these favourable conditions in these habitats. Overhoff, Freckman & Virginia (1993) found that temperatures of 10°C were required for growth of Scottnema lindsayae , the most dominant Antarctic nematodes adapted to cold soils – a temperature unlikely achieved in ice‐bound cryoconite holes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, nematodes survive freezing and desiccation in Antarctic soils through dormancy but reproduce when water and temperature conditions are favourable (Wharton, 2003). The presence of nematodes overlying glaciers in supraglacial debris (Azzoni et al ., 2015) and in glacier mice (Coulson & Midgley, 2012) indicates the presence of these favourable conditions in these habitats. Overhoff, Freckman & Virginia (1993) found that temperatures of 10°C were required for growth of Scottnema lindsayae , the most dominant Antarctic nematodes adapted to cold soils – a temperature unlikely achieved in ice‐bound cryoconite holes.…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes have been reported in supraglacial gravel in the Alps by Azzoni et al . (2015) and in moss balls (so‐called ‘glacier mice’) in Iceland by Coulson & Midgley (2012). Additionally, Schwarz et al .…”
Section: Introductionmentioning
confidence: 99%
“…In four-year-old soil at Hardangerjøkulen glacier in Norway, both Nematoda, Tardigrada, and Rotifera have been documented (Magnusson, Willassen and Hågvar, unpublished). Nematoda and Rotifera have been studied on supraglacial debris of two Alpine debris-covered glacier [70].…”
Section: Suggestions For Further Studiesmentioning
confidence: 99%
“…Spatial distribution of ground-dwelling arthropods is mainly determined by site age (time since deglaciation), with its related local fine-scale environment conditions, such as soil grain size, vegetation cover, and/or soil organic matter (see, Kaufmann, 2001;Brambilla & Gobbi, 2014;Tampucci et al, 2015). More recently, attention has shifted from the glacier forelands to the surface of debris-covered glaciers, because of the emerging interest of debris-covered glaciers as suitable habitats for micro-, meso-and macro-fauna and plant life (Caccianiga et al, 2011;Gobbi et al, 2011;Azzoni et al, 2015). Debris-covered glaciers are formed by frequent slipping and casting of deposits creating large quantities of stony material which covers the glacier surface, in particular on the ablation area (Citterio et al, 2007), and these have increased significantly during the last decade.…”
Section: Introductionmentioning
confidence: 99%